Structural Behavior of Strand Reinforced Concrete Members without Prestressing - Al Hawarneh, Alaa Maher (2016)
A Master of Science thesis in Civil Engineering by Alaa Maher Al Hawarneh entitled, "Structural Behavior of Strand Reinforced Concrete Members without Prestressing," submitted in December 2016. Thesis advisor is Dr. Sami Tabsh. Soft and hard copy available.